1997
DOI: 10.1111/j.1365-2222.1997.tb00740.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of serum eosinophil cationic protein (ECP) in the management of steroid therapy in chronic asthma

Abstract: From this observational study it is concluded that adjusting steroid therapy guided by serum ECP-level may be helpful in tailoring asthma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…Lower Gecp in our studied group was probably the result of the heterogeneity of the given group related to the severity and exacerbation of the disease. Geometric mean of ECP in our studied group (3.056 mg/L) was compatible with the control values (4.4 mg/L) of the producer of the serum ECP testing commercial kit, as well as with the reference data (5,9). Ahlstedt et al (10) reported that Gecp=3'5 mg/L in healthy persons, while somewhat higher values were found in children: 6.5 mg/L (11).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Lower Gecp in our studied group was probably the result of the heterogeneity of the given group related to the severity and exacerbation of the disease. Geometric mean of ECP in our studied group (3.056 mg/L) was compatible with the control values (4.4 mg/L) of the producer of the serum ECP testing commercial kit, as well as with the reference data (5,9). Ahlstedt et al (10) reported that Gecp=3'5 mg/L in healthy persons, while somewhat higher values were found in children: 6.5 mg/L (11).…”
Section: Discussionsupporting
confidence: 88%
“…ECP can be measured in body fluids and quantitated in serum as well, which is an accessible medium in clinical practice. Results from previous clinical evaluation of serum ECP in chronic asthma suggested that serum ECP is a sensitive marker of inflammatory airflow obstruction and that elevated levels denote patients at risk from inflammatory exacerbations, independent of atopic status, indicating the need to intensify treatment with corticosteroids (5).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical investigations have reported that eosinophils are increased in the sputum and bronchial biopsies of patients with AECOPD (31,32). Increased levels of ECP in serum (24,33), bronchoalveolar lavage fluid (34) and induced sputum (35) have been observed in patients with AECOPD. Hospers et al (20) proposed that peripheral blood eosinophilia may also lead to a higher mortality rate for patients with AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that serum levels of ECP are elevated in patients with asthma [33, 34, 35, 36, 37, 38]with respect to patients with rhinitis [18, 19, 20, 21]. Despite having been used for a number of years, the exact role for serum ECP measurements in asthma is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%